Hospital pharmacist’s roles and responsibilities with CAR-T medicines - María Estela Moreno-Martínez; Joan Vinent-Genestar; Carmen Muñoz-Sánchez; María Josep Carreras-Soler (Farmacia Hospitalaria)
The development and commercialization of cell therapy drugs with chimeric antigen receptor T cells (CAR-T) represent a new challenge for Spain’s hospital pharmacy. The aim of this article is to review the key aspects of these medicines and to describe the oncohematological pharmacist’s role within the ultidisciplinary clinical team. This includes the different phases in the transversal process that involves a therapy with CAR-T medicines, ranging from indication to short and long term follow-up of patients treated with this type of therapy, and emphasizing on the management of its main adverse effects. CAR-T therapy offers the hospital pharmacist the opportunity to work closely with the rest of the clinical professionals involved in the process, allowing their contribution to the development of procedures, clinical practice guidelines of global approach, and establishing starting points when facing future therapies of similar complexity –and even improving previously established basic processes–.